Teaching Offensive and Defensive Cyber Security in Schools using a Raspberry Pi Cyber Range (Journal of The Colloquium for Information Systems Security Education, 2023)
Computer Science as a subject is now appearing in more school curricula for GCSE and A level, with a growing demand for cyber security to be embedded within this teaching. Yet, teachers face challenges with limited time and resource for preparing practical materials to effectively convey the subject matter. We hosted a series of workshops designed to understand the challenges that teachers face in delivering cyber security education. We then worked with teachers to co-create practical learning resources that could be further developed as tailored lesson plans, as required for their students. In this paper, we report on the challenges highlighted by teachers, and we present a portable and isolated infrastructure for teaching the basics of offensive and defensive cyber security, as a co-created activity based on the teacher workshops. Whilst we present an example case study for red and blue team student engagement, we also reflect on the wide scope of topics and tools that students would be exposed to through this activity, and how this platform could then be generalised for further cyber security teaching.
Keywords: Cyber Security Education; Raspberry Pi; CyberRange